Herramientas usadas para la evaluación formativa automatizada en cursos de programación asistidos por computadora - Leytón-Yela, Ginna-Viviana; Bucheli-Guerrero, Victor-Andrés; Ordoñez-Erazo, Hugo-Armando (Revista Científica, 2022)
This study presents the use of tools for verifying the operation of automated feedback as implemented in programming courses. Educational environments offer the experience of summative and formative evaluation of computer programs, which is aimed at students. In this type of tool, students solve a programming task, which is automatically validated in order to generate grades and feedback. Regarding summative evaluation, a numerical or percentage grade is generated on whether the solution of a task is correct. In the case of formative evaluation, information is generated on errors or suggestions to be incorporated to the programs in order to improve learning. The employed tools are UNCode, Ask-Elle, and Nbgrader. In addition, some important remarks are made about some of the tools used for comparing programs and validating differences.